Measuring vulnerability to natural hazards towards disaster resilient societies - Birkmann, Jörn. (Tokyo United Nations University Press, 2006)
A seemingly non-stop series of disasters has shown that societies worldwide seem unprepared for the threats posed by natural hazards. The tragic impacts of these events drew short-term attention from policy makers, the media and the general public, but their response was too late to prevent serious harm. Societies need to measure their vulnerabilities in advance, and make adequate provisions. This publication presents a broad range of current approaches to measuring vulnerability and contains concrete experiences and examples from Africa, Asia, the Americas and Europe to illustrate the theoretical analyses.--Publisher's description.
Introduction / Janos J. Bogardi -- Basic principles and theoretical basis -- Measuring vulnerability to promote disaster-resilient societies: conceptual frameworks and definitions / Jörn Birkmann -- Indicators and criteria for measuring vulnerability: theoretical bases and requirements / Jörn Birkmann -- Social levels and hazard (in)dependence in determining vulnerability / Stefan Schneiderbauer, Daniele Ehrlich -- User needs: why we need indicators / Angela Queste, Peter Lauwe -- Vulnerability and environment -- Environmental components of vulnerability / Fabrice G. Renaud -- Human vulnerability to environmental change: an approach for UNEP's global environmental outlook (GEO) / Marcel T.J. Kok, Vishal Narain, Steven Wonink, Jill Jäger -- Global, national and sub-national index approaches -- Review of global risk index projects: Conclusions for sub-national and local approaches / Mark Pelling -- The disaster risk index: overview of a quantitative approach / Pascal Peduzzi -- Disaster risk hotspots: a project summary / Maxx Dilley -- A system of indicators for disaster risk management in the Americas / Omar D. Cardona -- Multi-risk assessment of Europe's regions / Stefan Greiving -- Disaster vulnerability assessment: the Tanzania experience / Robert B. Kiunsi, Manoris V. Meshak -- A human security index / Erich J. Plate -- Local vulnerability assessment -- Community-based disaster risk index: pilot implementation in Indonesia / Christina Bollin, Ria Hidajat -- Measuring vulnerability: the ADRC perspective for the theoretical basis and principles of indicator development / Masaru Arakida -- Vulnerability assessment: the sectoral approach / Juan Carlos Villagrán de León -- Self-assessment of coping capacity: participatory, proactive, and qualitative engagement of communities in their own risk management / Ben Wisner -- Measuring vulnerability in Sri Lanka at the local level / Jörn Birkmann, Nishara Fernando, Siri Hettige -- Institutional vulnerability, coping and lessons learned -- Assessing institutionalised capacities and practices to reduce the risks of flood disaster / Louis Lebel, Elena Nikitina, Vladimir Kotov, Jesse Manuta -- Public sector financial vulnerability to disasters: the IIASA CATSIM model / Reinhard Mechler, Stefan Hochrainer, Joanne Linnerooth-Bayer, Georg Pflug -- Text box effective measurement of vulnerability is essential to help those most in harm's way / Simon Horner -- Overcoming the black hole: outline for a quantitative model to compare coping capacities across countries / Peter Billing, Ulrike Madengruber -- A methodology for learning lessons: experiences at the European level / Elisabeth Krausmann, Fesil Mushtaq -- Conclusion and recommendation / Jörn Birkmann -- Core terminology of disaster reduction: a comparative glossary / Katharina Thywissen --List of contributors -- Index.
Dr. Vena Pearl Bongolan (recommending faculty)
Keywords: Natural disasters; Natural disaster warning systems